An analysis of the key role of human and technological development in the smart specialization of smart European regions. Issue 4 (1st October 2020) - Nevado Peña, Domingo; López Ruiz, Víctor Raúl; Alfaro Navarro, José Luis
ABSTRACT: The Europe 2020 development strategy prioritizes the so-called Smart Regions, reflecting the European Commission's commitment to geographical 'specialization.' Accordingly, the European regions have developed innovation strategies for smart specialization. A key element in these development strategies is the technological factor, which is clearly influenced by the level of human development in the region. This article analyses the convergence between citizens' capacities and technological development in a region. Specifically, we analyse 129 NUTS 2 regions in Europe, using official data provided by Eurostat. To measure human development, this article proposes a Smart Human Index based on a synthetic indicator incorporating three dimensions; in addition, we use two dimensions to construct an indicator of regional technological development. The results show that a region's technological capacity clearly depends on its inhabitants' degree of formal education, while their use of technologies depends on the citizens' degree of social openness and cultural level.